Neoclassical Concepts. (February 2015) - Leben, Derek
Abstract Linguistic theories of lexical semantics support a Neoclassical Theory of concepts, where entities like CAUSE, STATE, and MANNER serve as necessary conditions for the possession of individual event concepts. Not all concepts have a neoclassical structure, and whether or not words participate in regular linguistic patterns such as verbal alternations will be proposed as a probe for identifying whether their corresponding concepts do indeed have such structure. I show how the Neoclassical Theory supplements existing theories of concepts and supports a version of analyticity and conceptual analysis.